Some mythical issues surrounding Wundt’s status as the father of Experimental Psychology - Klappenbach, Hugo Alberto Arturo (2023)
The celebration of the 150th anniversary of the Grundzüge der physiologischen Psychologie, the 160th anniversary of the first edition of the Vorlesungen über die Menschen- und Tierseele and the 140th anniversary of the last volume of Die Logik requires consideration of the first major difficulty in dealing with Wundt´s work: the extraordinary breadth and complexity of his writings. Wundt´s own daughter, Wundt, compiled more than 490 publications totalling nearly 53,000 pages (Wundt, 1927).On this occasion I am interested in commemorating the 150th anniversary of the first edition of the Grundzüge. However, as Blumenthal and Araujo have pointed out, the first edition is evidence of a work in transition and it is only in the second edition of 1880 that certain concepts begin to mature. Moreover, it has also been argued that it is only after formalizing his entire philosophical system that Wundt fully matures his conception of psychology (Araujo, 2016). This can be seen in the Grudriss der Psychologie, the first edition of which dates from 1896, that is, after the Logik (Wundt, 1883), the Ethik (Wundt 1886) and the System der Philosophie (Wundt, 1889).